Rates of Diplopia in Ahmed FP7, Baerveldt 250, and 350 Glaucoma Patients Compared With Medical Controls. Issue 7 (27th July 2021) - Kilgore, Khin P.; Wang, Feng; Stern, Nicole C.; Sabbagh, Nouran; Jamali, Sepideh; White, Launia J.; Sit, Arthur J.; Bitrian, Elena; Roddy, Gavin W.; Mohney, Brian G.; Khanna, Cheryl L.
Abstract : Precis: Diplopia was present in 20% of patients with Ahmed FP7 (FP7) or Baerveldt 350 (B350), compared with 5% to 6% in those with Baerveldt 250 (B250) or controls, suggesting risk of diplopia should be included in preoperative counseling. Purpose: The purpose of this study was to examine the prevalence of diplopia and strabismus in patients with B250, B350, or FP7 glaucoma drainage devices (GDD). Materials and Methods: In this cohort study, glaucoma patients 18 years and above who had received, or would be receiving, a B250, B350, or FP7 GDD, and medically treated controls were consecutively enrolled from August 8, 2017, through July 31, 2019. The Diplopia Questionnaire was administered ≥30 days postoperatively, and upon enrollment to the controls. All diplopic patients underwent orthoptic measurements, which were reviewed by a strabismus specialist. Patients with GDDs in quadrants other than superotemporal, multiple GDDs, or scleral buckles were excluded. Bonferroni correction was applied for pairwise comparisons. Results: Diplopia was reported in 23/129 (17.8%) GDD patients and 5/99 (5.1%) control patients ( P =0.003): 8/35 (22.9%) FP7, 2/32 (6.3%) B250, and 13/62 (21.0%) B350, with significant differences between FP7 versus controls ( P =0.014) and B350 versus controls ( P =0.011). Diplopia was attributable to GDD in 2 FP7 (5.9%, 95% confidence interval: 0.7-19.2), 0 B250, and 4 B350 (6.5%, 95% confidence interval: 1.7-15.2) patients, without significant differences between the GDDs. Conclusions: Patients with the larger (B350) or the higher profile plate (FP7) GDDs were more likely to experience diplopia than controls, and diplopia was attributable to the GDD in 6% of patients with either a FP7 or a B350 GDD. Since diplopia can affect patients' quality of life, preoperative counseling for GDD surgery, particularly B350 and FP7, should include a discussion of the risk of diplopia.